Blaustein's pathology of the female genital tract - Kurman, Robert J.; Ronnett, Brigitte M.; Ellenson, Lora Hedrick (Springer, 2010)
Since the publication of the 1/e in 1977, Blaustein's Pathology of the Female Genital Tract has consolidated its position as the leading textbook of gynecological pathology. An essential reference for all pathologists and residents, this thoroughly updated Sixth Edition includes more than 1400 illustrations in color, informative tables and 22 revised chapters written by internationally recognized experts. Discussion of each specific entity is organized to include general information, etiology, and epidemiology followed by clinical features, pathologic findings, differential diagnosis, clinical behavior, and treatment. This clear organization is applied throughout the book and allows the reader to quickly access key information in every chapter. Blaustein's Pathology of the Female Genital Tract remains the gold-standard reference for practicing pathologists and trainees, as well as for obstetric/gynecology practitioners and residents.